Currículo educativo y grados académicos en tiempos posteriores a la Independencia: De la ilustración al liberalismo - Huaraj Acuña, Juan Carlos (Mercurio Peruano, 2020)
The present text belongs to the scope of History of Education, between the years of 1800 and 1840. It begins with a brief reference regarding to the contemporary historiography, emphasizing the topic mentioned. Then follows an analysis of some study plans proposed to the Supreme Government within the two decades which followed the Declaration of Peruvian Independence, and in both cases, their relationship to the Pontifical University of San Marcos in Lima, for the obtaining of the corresponding degrees, thus officially validating the studies conducted. In the case of the Convictorio Carolino –emblematic educational center during the times of the Colony, and consolidated during the times of the Republic– it is mainly focused in the curricular structures from 1830 to 1840. In the case of the Colegio de Ciencias de Ica (Ica School of Sciences), it highlights the way in which study plans for the Convictorio in Lima are taken as models to be followed by institutions within the country.